Determination of the economic role of creative industries in development of the national economy of ukraine - Nebava , Mykola; Yanan, Li (Scientific Journal of Bielsko-Biala School of Finance and Law, 2021)
The article identifies five infrastructural elements of creative development. It is proved that the formation of creativity by the state is a synchronous, multifaceted and time-consuming process. This process takes into account the interests of regions, creative industries and workers involved in this field. It is determined that the creative industries affect the size of the region's GDP, and stimulate the economic development of neighboring regions, and in general the economic growth of the national economy through direct, indirect and induced influences. The article investigates the approaches to define the terms "creative economy" and "creative industries". Based on European experience, it is proven that as for today there is a close connection between creative industries and spheres of human activity. It is found that the infrastructural components of creative industries are: developing of creativity policy, strengthening of organizational capacity, supporting of business incubators and accelerators, promoting of clusters and hubs, focusing on global markets. In addition, it is proven that creativity development directly affects development of the whole country through the creativity sector as an image tool of attracting investment to the country.